The susceptibility of hydrogen embrittlement of low alloy Cr-Mo steel tubing - Gojić, Mirko (Kovine zlitine tehnologije, 1993)
In the paper the results of research in the susceptibility of as-rolled and heat treated low alloy Cr-Mo (microalloy by Nb) tubing to hydrogen embrittlement by method of cathodic polarization are shown. The results show that quenching at 870°C (both in water and oil) and tempering at high temperature (720°C) attain excellent resistance to hydrogen embrittlement whichis indicated by a small embrittlement index (11.1-23.6%) by tough amall-dimple fractures and relatively small content of absorbed hydrogen (3.2-3.4 ppm) at the cathodoc polarization.
Keywords: jekla; nizkolegirana jekla; krom-molibdenova jekla; cevi; kaljenje; trdnost